When we hear them : attuning teachers to language-diverse learners - Tomlin, Antione D.; Andrews, Owen Silverman (Research, theory, and practice within academic affairs., 2024)
"This book puts forward practical tools and applicable theories for enhancing the listening skills and pedagogical approaches of teachers and educators in the context of language-minoritized and emergent multilingual learners. What does it mean for us to really hear them? How can we more fully facilitate inviting, celebratory, and sustaining learning spaces? Where and when should we assess and self-assess these skills and spaces? By asking these questions, we seek to upend deficit models of language learning and usage in order to attune practitioner-scholars to the powerful voices of language-diverse students in our classrooms, schools, and communities. This book is organized into three parts to help practitioner-scholars explore the space where theory meets practice to amplify the voices of language-minoritized learners"--